Close reading of the Bible - Coetzee, Johan (Old Testament essays, 1994)
Special Edition: Understanding the Old Testament in South Africa. 'Close reading', which as a technical term originated from the Anglo-Saxon world, is today connected to a variety of literary approaches, such as literary criticism, redaction criticism, rhetorical criticism, semiotics and structural methods. It focuses on a detailed analysis of the artistic and linguistic structure of a text as a whole.